CEGAH IKTERUS DENGAN MENINGKATKAN PENGETAHUAN IBU - Nursanti, Ida (MEDIA ILMU KESEHATAN, 2013)
Background: Neonatal jaundice (icterus neonatorum) is acommon problem in infants in the first weekafter birth. Sixty percents of healthy infants born full term are at risk of neonatal jaundice. Bilirubinen cephalopathy causes severe jaundice/kernicterus and the baby suffering from kernicterus willexperience impaired growth and development. The Health education for mother is very important for improving the knowledge, disease prevention, and health improvement. Mother is expected to know and recognize the signsof icterus neonatorum so that shecan bring the baby to get help at the health facilityas fast as possible. Objective:To reduce the risk of neonatal jaundice in Yogyakarta; to know the incidence of neonatal jaundice in breastfed infants, the effect of health education against the risk of neonatal jaundice; Methods: This study was anobservational study with across-sectional design. Sampling used purposive sampling. The sample size was 115 pairs of mother-infant who met the inclusion and exclusion criteria. The data was collected using monitoring sheet sand check lists. Hypothesis test used chi-square with p<0.05 and 95% Confidence Interval. Analysis of data used univari able and bivari able analyses. Results: There was adifference in the proportion of the riskof neonatal jaundice between mothers who received good health education and those who received in adequate health education. Mothers who received in adequate health education were more likely to have chances of neonatal jaundice by 2.1 times compared with mothers who received ade quate health education. Conclusion: Mothers who received in adequate health education had ahigher risk for neonatal jaundicetooccur compared with those who received ade quate health education. Keyword: Healthy born baby, health education, neonatal jaundice (icterus neonatorum)